Museum encounters: a choreography of visitors' bodies in interaction. (4th July 2019) - Diamantopoulou, Sophia; Christidou, Dimitra
ABSTRACT: By viewing the museum experience as inextricably linked to an interactive nexus of bodies and objects arranged in the museum space, this paper foregrounds the significance of movement in the shaping of museum encounters. Informed by the fields of dance, symbolic interactionism and multimodal social semiotics, it introduces a conceptualisation of visitors' movement as choreography unfolding either in compliance with the museum 'script' (scripted choreographies), or in response to prompts from other visitors sharing the same space (improvised choreographies). Attending to visitors' positioning and alignment as key resources of movement, the analysis of video data from two London galleries illustrates how visitors oscillate between performing 'scripted choreographies' and 'improvised choreographies' through shifts in positioning and alignment, while being spectators of other visitors' choreographies. Both kinds of choreographies are continuously shaped in interaction with the 'scripted' museum stage and other visitors' 'scripted' and 'improvised choreographies'.